Upaya Peningkatan Minat Belajar Pada Masa Pandemi Covid 19 di Desa Kutomulyo - Endang Haryati; Arif Fachrian; Fahmi Sulaiman (Yayasan Literasi Sains Indonesia, 2022)
Shaping and redeveloping a sense of interest in learning in every child during the covid-19 pandemic which is one of the main problems. During the Covid-19 Pandemic, learning hours have also reduced so that children are lazy to study and prefer to play. This causes laziness in children and does not provide enthusiasm for learning. The purpose of implementing community service is intended for children to realize the importance of learning for their education, not only children but also parents to monitor their children's learning more and Community Service is intended to provide more lessons in their free time. The target achieved in this community service is to increase children's interest in learning during the COVID-19 pandemic and increase their language knowledge. The method used is to provide an explanation of how to read and count and speak English correctly, a socialization session in the form of questions and answers about the material presented, and evaluating the ability of village children by holding a competition at the end of the meeting. Kutomulyo Dusun 1, Sibiru-biru District, is to see how far the children in Kotamulyo village understand the lessons that have been conveyed by their teachers through online learning, and we can also improve the learning abilities of children in Kutomulyo village.